Sulfur and copper isotopic signatures of chalcopyrite at Kalatongke and Baishiquan: Insights into the origin of magmatic Ni-Cu sulfide deposits. (15th April 2020) - Tang, Dongmei; Qin, Kezhang; Su, Benxun; Mao, Yajing; Evans, Noreen J.; Niu, Yanjie; Kang, Zhen
Abstract: Sulfide Cu isotope systematic has been used as a metallogenic tracer in various deposits; however, only rarely in magmatic Ni-Cu sulfide deposits. Here we present chalcopyrite δ 34 S and δ 65 Cu data for the Kalatongke and Baishiquan Ni-Cu sulfide deposits in the Central Asian Orogenic Belt. The Kalatongke deposit yields δ 34 S of −3.99‰ to 3.30‰ and δ 65 Cu of −1.32‰ to 0.07‰, whereas chalcopyrite from the Baishiquan deposit has δ 34 S values ranging from 1.70‰ to 4.98‰ and δ 65 Cu from −0.40‰ to 0.59‰. These isotopic ratios show no correlation with intrusion/orebody shape, location of sample in the orebody, lithofacies or type of mineralization. Based on Kalatongke and Baishiquan δ 34 S data, our multicomponent modeling suggests that, with an increase in the relative crustal component contribution, the measured δ 34 S values in sulfide ores approach the value of the contaminant. Mass ratios (R′) of silicate magma/(xenomelt + sulfide xenomelt + resitite + crystalline olivine) of 250–800 in the Kalatongke and 10–1000 in the Baishiquan deposit, yield δ 34 S values of −1.78‰ to 1.74‰ and 1.70‰ to 4.98‰ in these deposits. Contamination by host tuff and shale material with δ 34 S values of −7.2‰ to 3.3‰ reasonably explains the negative δ 34 S in the Kalatongke ores. A lack of correlation between the Kalatongke and Baishiquan chalcopyrite δ 65 Cu values and Cu or S contents (or Cu/Ni ratios) indicates that Cu isotopic fractionation was not controlled by sulfide fractional crystallization, but instead by contamination and the mantle source. Multicomponent modeling shows that an R′ factor between 10 and 1000 can reproduce most δ 65 Cu signatures in sulfide ores from the Kalatongke and Baishiquan deposits, with the exception of a few negative δ 65 Cu values. Undetected contamination and heterogeneous mantle resulting from different degrees of partial melting and metasomatism in the mantle source may explain these negative values and the wide range of δ 65 Cu noted in magmatic sulfide deposits worldwide. The Cu and S isotopes in sulfide from the magmatic Ni-Cu sulfide deposits can be utilized as indicators of crustal contamination and the nature of the mantle source.